2015
DOI: 10.7454/mssh.v19i2.3478
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Place among Adolescents: Factors Influencing the Place Attachment on Shopping Malls

Abstract: This research aims to find the push factors that create relationships between youth and shopping centers and examines how different mall environments also help create different emotional bonds towards the malls. This topic is further observed with an explorative study that obtained its primary data from interviews and secondary data from various supporting literatures as well as from a number of observations. The informants were 15 visitors of each of the following shopping centers: Tunjungan Plaza and Ciputra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…Kang et al (1996) evaluated that the teen segment had stronger shopping motivations compared to others age segments. Kusumowidagdo et al (2015) described the push items that determine relationships between youth and shopping centers. Dahan-Oliel et al (2015) researched the needs and expectations of adolescents with disabilities from the shopping mall and determined the necessary changes for the participation of youth with disabilities within a mall.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Kang et al (1996) evaluated that the teen segment had stronger shopping motivations compared to others age segments. Kusumowidagdo et al (2015) described the push items that determine relationships between youth and shopping centers. Dahan-Oliel et al (2015) researched the needs and expectations of adolescents with disabilities from the shopping mall and determined the necessary changes for the participation of youth with disabilities within a mall.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The narratives found in the literature surrounding the marginalisation, and exclusion of young people from public spaces (Abbott-Chapman & Robertson, 2001;Cockcroft et al, 2016;Malone, 2002) (Karsten, 2003;Kusumowidagdo et al, 2015), were largely not reflected in the findings of this study. This could be the result of both changed perceptions of behaviour due to game dynamics (i.e.…”
Section: Marginalisation and Exclusionmentioning
confidence: 58%
“…Regarding shopping areas, research into sense of place is limited. Kusumowidagdo et al (2015) have studied the factors that influence adolescents' place attachment to shopping malls. They found that physical and social factors, memories and experience, familiarity, novelty, place satisfaction, interaction and activity features, time, and branding and promotion play a role.…”
Section: Sense Of Placementioning
confidence: 99%
“…On that understanding, this study contributes to that emerging field. While it has been found that shopping area characteristics can contribute positively or negatively to experiences of a sense of place (Kusumowidagdo et al, 2015;Shamsuddin & Ujang, 2008), the literature does not explore the extent to which sense of place is related to shopping behaviour within physical shopping areas.…”
Section: Introductionmentioning
confidence: 99%